PhilipVerhagen, Axel. G. Posluschny in Alžbêta Danielsová (ur.): Go Your Own Least Cost Path. Spatial technology and archaeological interpretation. Proceedings of the GIS session at EAA 2009, Riva del Garda, 2011 - Štular, Benjamin (Arheološki vestnik, 2012)
/